Switching of macromolecular ligand display by thermoresponsive polymers mediates endocytosis of multi-conjugate nanoparticles - Sayers, Edward; Magnusson, Johannes Pall; Moody, Paul; Mastrotto, Francesca; Conte, Claudia; Brazzale, Chiara; Borri, Paola; Caliceti, Paolo; Watson, Peter; Mantovani, Giuseppe; Aylott, Jonathan W.; Salmaso, Stefano; et al. (American Chemical Society, 2018)
Ligand-mediated targeting and internalization of plasma membrane receptors is central to cellular function. These types of receptors have accordingly been investigated as targets to facilitate entry of diagnostic and therapeutic constructs into cells. However, there remains a need to characterize how receptor targeting agents on nanoparticles interact at surface receptors and whether it is possible to control these interactions via exogenous stimuli. Here, we describe the switchable display of the iron-transporting protein, transferrin (Tf), at the surface of thermoresponsive polymer-coated gold nanoparticles, and show that internalization of the coated nanoparticles into target cells changes across temperature ranges over which transferrin is expected to be sterically ‘hidden’ by an extended polymer chain and then ‘revealed’ by polymer chain collapse. The switching process is dependent on the numbers of transferrin molecules and thermoresponsive polymer chains attached, and whether the assay temperature is above or below the transition temperatures of the responsive polymers at the nanoparticle surfaces. Significantly, however, the control of internalization is critically reliant on overall nanoparticle colloidal stability while the thermoresponsive component of the surface undergoes conformational change. The data show that the cell entry function of complex and large biomolecule ligands can be modulated by polymer-induced accessibility change, but that a simple ‘hide and reveal’ mechanism for ligand display following polymer chain collapse is insufficient to account for nanoparticle uptake and subsequent intracellular trafficking.